MARGINALISASI WANITA DIBALIK BERITA (ANALISIS WACANA KRITIS SARA MILLS MARGINALISASI WANITA DALAM BERITA ONLINE UNGKAP SYARAT STAYCATION DEMI PERPANJANG KONRAK) - Hidayat; Agus Hamdani (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2023)
This research discusses sexual harassment that occurs among women in online media coverage. Good media can provide balanced and informative information. Various reports related to sexual harassment experienced by women often represent someone within a discourse. Currently, the exploitation of women is carried out through more intellectual and sophisticated ways, one of which is through discourse expressed in mass media. Women in the media are positioned prominently visually but marginalized in meaning. If left unchecked, this will further emphasize the gender differences between women and men, resulting in an increased potential for gender oppression with women as the victims. The issue addressed in this research is the discourse analysis using Sara Mills' theory. Sara Mills' discussion on discourse theory revolves around feminist discourse as its main focus, addressing women's issues such as how women are portrayed in the news. The research method used in this study is literature review. The results of this study conclude that the texts exhibit bias in representing women in news texts across four different media sources.